Revisiting the effect of statutory pension ages on the participation rate - Turner, David (OECD Economics Department Working Papers, 2020)
Many OECD governments have enacted, or are contemplating, future increases in statutory pension ages, sometimes provoking vociferous political opposition. Empirical cross-country estimation work consistently finds that coefficients on statutory pension ages are positive and highly statistically significant in explaining labour-force participation at older ages. There is also some consistency in the magnitude of the estimated effects across studies, although this magnitude seems surprisingly modest when translated into the implied effect on average retirement ages: an increase in statutory pension ages by one year is typically estimated to increase the average effective retirement age by only about two months